Performance of locally developed sunflower (Helianthus annuus L.) hybrids under irrigation - Mohamed, Salah B.; Abdella, Abdel Wahab H. (المجلة الزراعية, 2007)
A field experiment was carried out at two locations, New Halfa and Rahad, for two cropping seasons, summer (2003/04) and winter (2004/05) at each location in a randomized complete block design with four replicates, to estimate the phenotypic and genotypic variability, heritability in broad sense and genetic advance for yield, yield components and other agronomic characters among 20 locally developed sunflower ( Helianthus annuus L.) hybrids. Highly significant differences found between the evaluated hybrids for almost all characters at the four environments, except plant height at New Halfa, in summer, 1000- seed weight and seed yield at both locations in winter. Most of the variation for the morphological traits was due to genetic factors, whereas, the variation in yield and its components was due to environmental factors. High heritability estimate (>60 %) coupled with low genetic advance for the morphological characters indicate epistatic and dominance nature of inheritance, while, the low heritability (<60 %) coupled with high genetic advance for yield and its components, would indicate additive nature of inheritance. Therefore, direct selection for the morpholo-gical traits, based on the phenotype, among the hybrids may be effective, while selection for yield and yield components may not be effective. Thus, there is a need for a mechanism, other than simple selection, to improve yield in sunflower.